FORMS OF SYNTHESIS OF ARTS OF CHINESE ARCHITECTURE: Array - Changzhi, Wu (Municipal economy of cities. Series: «Economy science», 2021)
The article examines the synthesis of arts on the example of Chinese architecture. General historical questions of the development of Chinese culture and various arts during historical evolution are raising. Philosophical and religious positions of culture are distinguishing, which are identifying with the development of art. The question arises of the lack of a full analysis of ancient Chinese art for all types of artistic creativity that were developing during cultural development and formation: architecture, painting, calligraphy, music, sculpture, dance, and so on. A number of scholars who have developed methods of approaches to the systematization and study of the synthesis of the arts of ancient Chinese culture throughout its development are presenting. A number of techniques in painting and calligraphy that have a direct impact on the formation of the Chinese architectural environment are analyzing. These methodical conclusions can be useful in planning the activities of various organizational departments of architectural education and science. Problem statement: it became necessary to analyze and describe the methods and principles of organizing forms of art synthesis in Chinese architecture. Objective of the article: analyze the impact of forms of art synthesis in Chinese architecture. There is describing that the most important art form in China is painting. It is thanks to its compositional, color and harmonic laws that the general cultural world of ancient China is building. Color relationships, combinations with nature - all this through painting builds the canonical laws of architecture, music, dance, calligraphy, etc., taking into account national authenticity. It becomes the central core of the synthesis of Chinese art, generating its various forms for individual regions. In architecture, the action of forms of synthesis of Chinese arts is embodying through the organization of plasticity of the building, interior and exterior space, the ratio of small and large forms, and the location of accents. Experienced predecessors should be a role model for modern architects and artists. The combination of long-standing traditions of "synthesis of arts" with modern production technologies, as well as creative ideas of architects and artists of the XXI century can give new vectors of development of Chinese architecture and art science.